Tissue engineering - Blitterswijk, Clemens A. van (Academic, 2007)
Tissue Engineering is the most comprehensive text available for upper level undergraduate and graduate level courses in tissue engineering within bioengineering, medical and research departments. It surpasses other books that merely provide a collection of research and protocols and presents an insightful examination of the different aspects of tissue engineering. Full-color throughout, extensive examples, and ancillary material optimize the usefulness of this book for students and professors. Covers all the essentials from tissue homeostasis and biocompatibility to cardiovascular engineering and regulations Contains 24 chapters, each designed for a session in a series of lectures. Provides ancillary material including full color pictures and videos to support lectures.